Efficacy and Safety of Ambroxol Lozenges in the Treatment of Acute Uncomplicated Sore Throat – a Pooled Analysis - de Mey, C.; Koelsch, S.; Richter, E.; Pohlmann, T.; Sousa, R. (Drug Research, 2016)
A pooled analysis is presented of 7 placebo-controlled RCT that investigated lozenges containing ambroxol for pain relief in acute sore throat.2 242 patients were treated with different ambroxol doses or control treatments, 2 183 were evaluable for efficacy. The present analysis is focused on the recommended dose of 20 mg (AXL20): 856 patients were treated with AXL20, 847 with matched placebo lozenges (PL).The average reduction in pain intensity over the first 3 h after the first AXL20 ranged from 38% to 52% of the maximum achievable effect (MAE). The overall treatment difference between AXL20 and PL was 11% (95% CI: 8–13%) of the MAE (post-hoc meta-analysis). The corresponding NNT was 6.0 (CI: 4.7–8.4) for an average pain reduction from baseline of 33% of the MAE over the first 3 h.71.9, 79.0, and 85.3% of the AXL20-patients scored the efficacy as “very good or good” at the end of the 1st, 2nd and 3rd day, respectively, vs. 57.5, 64.4, and 70.4% of the PL-patients resulting in odds ratios of 1.9 (CI: 1.5–2.3) for the 1st, 2.1 (CI: 1.7–2.6) for the 2nd and 2.43 (CI: 1.8–3.3) for the 3rd day.At the end of treatment ‘no redness’ or ‘slightly red’ was scored on pharyngeal inspection in 84.4% and 77.3% of AXL20- and PL-patients (OR: 1.6, CI: 1.3–1.9).AXL20-treatment was well tolerated and is safe and efficacious for acute uncomplicated sore throat of recent onset in adolescent and adult patients.
Keywords: drug research; clinical trials; local anaesthetics